Analysis of High-Dose N-Acetylcysteine Administration of Kidney Function F Patients Diagnosed with Acute Kidney Injury For The Period January – December 2021 at RSPON Jakarta - Nurul Ulya (Asian Journal of Social and Humanities, 2024)
In the last decades, the incidence of Acute Kidney Injury (AKI) has been increasing and resulting in prolonged adverse effects. The success of AKI therapy has not been maximally achieved, considering that AKI management is currently still conducted based on the arising causes and symptoms. The AKI management requires to be increasingly developed due to the serious effects of AKI. Thus, supportive therapy is needed to increase the cure rate for AKI. One of the treatment options is high-dose administration of N-acetylcysteine antioxidant therapy of 5000 mg. The research aims to determine the effect of high-dose administration of N-acetylcysteine by 5000 mg iv on kidney function in patients diagnosed with AKI based on creatinine serum, GFR, and urea. The research was a descriptive-analytic with retrospective cross-sectional. Further, the research employed medical data records. Differential analysis of kidney function with the laboratory results of urea, creatinine, and GFR parameters in AKI patients. It was performed on both the control and the testes groups, pre- and post-administration of a high-dose of N-acetylcysteine by 5000 mg iv. In addition, data were analyzed by bivariate with the paired t-test and independent t-test for differences between groups at p ? 0.05. There were 60 total samples, which were divided into 30 AKI patients, administered with N-acetylcysteine, and 30 patients, treated with N-acetylcysteine. The relationship analysis of pre- and post-administration of N-acetylcysteine in each group demonstrated significant differences in the tested group, such as the values of Creatinine Serum (p = 0.002) and GFR (p = 0.001).